The Main Messages of Modern Ukrainian Political Cartoons as Humorous Creolized Text - Shevchuk, Tetyana (Journal of Danubian Studies and Research, 2023)
The modern Russian-Ukrainian war revived the genre of political caricature as humorous creolized text. This allows conveying the important political, social and philosophical messages to a wider audience in an entertaining format through satirical drawings, in particular to actively influence the formation of public opinion. The illustrations are taken from the authors’ Facebook pages. These works have been posted in public places by their authors and are available for free viewing.